Students Perception on Teacher's Teaching Styles Affect Their Interest in Reading English Text - Davi Sulthon Al-Baihaqi; Ahmad Jainul Qurota A'yun; Fadillah Amri Firdaus; Akmalludin Purwo Widodo; Nida Husna; Didin Nuruddin Hidayat (Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to investigate English teachers' teaching styles and their impact on students' interest in English texts. This study was conducted in one of the universities in Jakarta to find out whether students' perceptions of teachers' teaching styles affect their interest in reading English texts. This study is a qualitative research. The participants of this study were 10 students in the English Education Department who had completed the first to third semester reading course. The research data were collected through interviews. The qualitative data were analyzed using Miles and Huberman's theory. The results show that the teacher's teaching style has a clear impact on improving reading interest. In this case, as long as the teacher's reading style maintains active interaction, provides structure, feedback, and gives clear explanations, it can have an impact on students' interest in English texts.